Exploring interindividual differences in fasting and postprandial insulin sensitivity adaptations in response to sprint interval exercise training - Richard Metcalfe (European Journal of Sport Science, 2022)
Previous studies have concluded that wide variance in changes in insulin sensitivity markers following exercise training demonstrates heterogeneity in individual trainability. However, these studies frequently don’t account for technical, biological, and random within-subject measurement error. We used the standard deviation of individual responses (SDIR) to determine whether interindividual variability in trainability exists for fasting and postprandial insulin sensitivity outcomes following low-volume sprint interval training (SIT). We pooled data from 63 untrained participants who completed 6 weeks of SIT (n=49; VO2max: 35 (7) mL⋅kg-1⋅min-1) or acted as no-intervention controls (n=14; VO2max: 34 (6) mL⋅kg-1⋅min-1). Fasting and oral glucose tolerance test (OGTT)-derived measures of insulin sensitivity were measured pre- and post-intervention. SDIR values were positive and exceeded a small effect size threshold for changes in fasting glucose (SDIR=0.27 [95%CI 0.07,0.38] mmol⋅L-1), 2-h OGTT glucose (SDIR=0.89 [0.22,1.23] mmol⋅L-1), glucose area-under-the-curve (SDIR=66.4 [-81.5,124.3] mmol⋅L-1⋅120min-1) and The Cederholm Index (SDIR=7.2 [-16.0,19.0] mg⋅l2⋅mmol-1⋅mU-1⋅min-1), suggesting meaningful individual responses to SIT, whilst SDIR values were negative for fasting insulin, fasting insulin resistance and insulin AUC. For all variables, the 95% CIs were wide and/or crossed zero, highlighting uncertainty about the existence of true interindividual differences in exercise trainability. Only 2-22% of participants could be classified as responders or non-responders with more than 95% certainty. Our findings demonstrate it cannot be assumed that variation in changes in insulin sensitivity following SIT is attributable to inherent differences in trainability, and reiterate the importance of accounting for technical, biological, and random error when examining heterogeneity in health-related training adaptations.